Constructing research questions doing interesting research - Alvesson, Mats 1956-; Sandberg, Jörgen (Los Angeles, California SAGE, 2013)
All researchers want to produce interesting and influential theories. A key step in all theory development is formulating innovative research questions that will result in interesting and significant research. Traditional textbooks on research methods tend to ignore, or gloss over, actual ways of constructing research questions. In this text, Alvesson and Sandberg develop a methodology for identifying and challenging assumptions underlying existing theories and generating research questions, using examples from across the social sciences.
Keywords: Social sciences -- Research -- Methodology